Elementos sobre os processos de construção do briefing: o caso Saccaro - Damin, Vania Maria (Universidade do Vale do Rio dos Sinos, 2010)
The present study deals with the relationship between the furniture industry context of the Bento Gonçalves city Furniture Pole and design as a competitive differential for this sector. Considering the complexity and the essential role of problem construction in the project process we take as a guideline that the competitive differential can be achieved, among other factors, through the participation of design in the briefing construction for new products and services. The research will be developed in Caxias do Sul city (RS) which belongs to this pole. In order to do so, a literature review was made in which we attempted to contextualize the furniture industry, emphasizing its main characteristics and importance as economic sector, as well as to approach the main contributions of design in the ambit of this industry. The field research will be carried out in the mentioned pole through depth interviews applied at the SM Gestão e Negócios company, which detains the Saccaro brand, part of the residential furniture segment, whose consuming target group is the medium-sized "A" class. With this research we wish to obtain data that, being systematized, analyzed and interpreted, will allow us to trace a profile of the selected segment of the researched pole, contributing to identify whether the influence of the designer in the briefing elaboration can be a differentiation and competitiveness factor as well as to establish interrelations between design and competitive differentiation.
Keywords: Indústria moveleira; Design; Projeto; Briefing; Diferenciação; Competitividade; Furniture Industry; Project; Differentiation; Competitiveness; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial